The development, implementation and evaluation of a shared care model of nursing in a tertiary hospital using participatory action research and practice development - Kidd, Heather M. (Curtin University, 2012)
For the last decade there has been a growing body of international evidence demonstrating the adverse effects on patient care caused by the continued international shortage of registered nurses (RN). One solution being explored in hospitals in Australia is to change their staffing mix by recruiting more graduate RNs, enrolled nurses (EN) and introducing unregulated workers (nursing assistants) as a strategy to increase the nursing workforce. To assist with managing the varied skill mix, hospitals have investigated team nursing as an alternative to the established RN dependent patient allocation model of nursing delivery. There is no conclusive evidence that demonstrates the impact of one model of care as compared to another in terms of satisfaction, quality and cost of care.Major deficits exist in team based nursing research. These are largely due to the small scale of the studies; focus on its use in medical and surgical wards and limited evaluation measures for staff and patients’ satisfaction and patient outcomes. Consequently, these studies have not demonstrated team nursing as an effective model in supporting nurses deliver care nor as a model that ensures the provision of quality patient care. This study addresses these deficits and provides a strong evidence base for the use of team based nursing in tertiary hospitals to both support nursing staff and contribute to positive patient outcomes.The purpose of this study was to develop, implement and evaluate a team based model (subsequently coined Shared Care Model or SCM), that supported the different levels of skill mix in the provision of safe care for patients admitted to 21 nominated wards (571 beds) at the study hospital. The impact the SCM had on nurses’ workload, team approach to organisation and provision of nursing care, culture of support, nursing rounds, bedside and board handover were investigated. In addition, the impact the SCM had on patient satisfaction, patient complaints and adverse incidents was investigated.The philosophical base for this study was critical social theory and the methodology participatory action research (PAR), underpinned by principles and processes of emancipatory practice development (ePD). Data instruments included validated staff and patient satisfaction questionnaires and the study hospital’s clinical incident and complaint management’s electronic systems and databases.The major findings of the study were statistically significant increases in learning opportunities and more manageable workloads associated with a less experienced nurse working with a more experienced nurse. However, this did not have an overall statistically significant effect on improving the culture of support nor ensuring manageable workloads. Statistically significant reductions were found in the four major adverse events measured of medications, falls, injuries and behaviour. Patient satisfaction was statistically significantly improved in relation to discharge planning and there were significant reductions in complaints associated with the manner in which patient were treated by nurses. Despite maintaining high levels of patient satisfaction throughout the study period there were statistically significantly more complaints in relation to the quality of clinical care. These findings establish that combinations of RNs of different levels of experience when working together as a team either in pairs or with unregistered staff provides safe patient care for a diverse range of clinical specialities.